اتجاهات طلاب كلية التربية الرياضية نحو الاختلاط في المحاضرات العملية - ماضي, أنجيلا (Latakia University Journal -Medical Sciences Series, 2017)
انطلاقاً من حاجة كلية التربية الرياضية في جامعة تشرين لتطبيق الاختلاط بين الجنسين خلال ممارستهم للأنشطة الرياضية في محاضراتهم العملية وبهدف معرفة اتجاهات الطلاب نحو هذا الاختلاط, كان هذا البحث الذي يفتح باب النقاش أمام موضوع الاختلاط بين الجنسين بإيجابياته وسلبياته في أثناء ممارستهم للأنشطة الرياضية المختلفة والتساؤل عن الفروق بين اتجاهات الذكور والإناث وفيما إذا كان لطلاب السنتين الأولى والثانية, المطبق فيهما الاختلاط إدارياً, موقفاً أكثر إيجابيةً منه لدى طلاب السنتين الثالثة والرابعة.من هنا قمنا بتوزيع مقياس مقنن لهذا الغرض على عينة من طلاب كلية التربية الرياضية تكونت من 291 طالبا وطالبة من مختلف السنوات ضمن العام الدراسي 2015- 2016.أظهرت النتائج أن غالبية الطلاب تتبنى موقفاً إيجابياً تجاه الاختلاط بين الجنسين في محاضراتهم العملية. كما لم تظهر أي أثر لمتغير الجنس في اتجاهاتهم وبينت أيضا عدم وجود أية فروق دالة إحصائيا بين اتجاهات كل من طلاب السنتين الأولى والثانية والثالثة والرابعة تجاه هذا الاختلاط. The present study comes from the need of the faculty of Sport Education to apply coeducation among genders, especially in their practical lectures, and in order to know the students' attitudes towards this coeducation. This is a search that opens the door to debate the subject of coeducation between genders with both negative and positive aspects, and highlights the differences between both male and female students, and whether first and second year students (where coeducation is practically applied) have more positive attitude than third and fourth year ones.To support this purpose, a valid questionnaire was distributed on a sample consisted of 291 students from different years within the academic year 2015-2016. From all above, results show that the majority of students adopt a positive attitude towards coeducation between genders in their practical lectures. As no effect has appeared to the attitudes of variable-sex. Also, it show that there are no statistically significant differences between the trends of first and second year students with the third and fourth year ones towards this coeducation.